Quality analysis of fermented wine with different varieties of fresh jujubes - YIN Rong, WANG Junyu, RU Jiansheng, YANG Deyu, LIANG Zhihong (Zhongguo niangzao)
To screen suitable varieties for jujube wine, fermented jujube wine was prepared using different varieties of fresh jujubes (Hama jujube, You Jujube, Fuping jujube, Jun jujube, Hui jujube, and Huping jujube) as raw materials. The basic physiochemical indicators, organic acid content and volatile flavor substances were determined. Based on the volatile flavor substances, different wine samples were analyzed by partial least squares-discriminant analysis (PLS-DA). The key volatile flavor substances were screened combined with the odor activity value (OAV), and the sensory quality of jujube wine was analyzed. The results showed that there were certain differences in the physicochemical indicators of fermented wine with different varieties of jujube. The alcohol content of Huping jujube wine was the highest (12%vol), the sugar-acid ratio was the lowest (0.24), and the citric acid and succinic acid contents were the highest (0.18 g/L, 0.99 g/L). The contents of ascorbic acid and total phenol in the Hama jujube wine were the highest (11.25 mg/L, 0.66 mg/L). Succinic acid, lactic acid and acetic acid were common organic acids in the fermented wine of fresh jujubes, and mainly lactic acid and acetic acid with contents of 1.15-5.49 g/L and 0.89-2.37 g/L, respectively. A total of 45 volatile flavor substances were detected in fermented wine with different varieties of fresh jujubes, among which there were 6 alcohols, 5 aldehydes, 26 esters, 4 alkanes and 4 other types. PLS-DA could distinguish different varieties of jujube wine samples based on volatile flavor substances. Among the 6 kinds of jujube fermented wines, there were a total of 9 key volatile flavor substances (OAV>1). In conclusion, Hama jujubes and Huping jujubes wine had distinct style and were more suitable for brewing jujube wine.